Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

Evaluation of ballistics euthanasia applied to stranded cetaceans using ethological and post-mortem computed tomography assessment - Rebecca M. Boys; Brian C. W. Kot; Gordon Lye; Ngaio J. Beausoleil; Stuart Hunter; Karen A. Stockin (Veterinary Research Communications, 2024)
Debilitated stranded cetaceans with low survival likelihood, may require euthanasia to avoid further suffering. Euthanasia can involve chemical or physical methods, including ballistics. Ballistics should cause instantaneous, permanent insensibility through brainstem disruption. Despite wide application, there is limited understanding of ballistics-related welfare outcomes. We opportunistically examined behaviour of three maternally-dependent cetaceans following shooting and the related cranial disruption post-mortem using computed tomography (PMCT). Our aim was to understand whether a ‘humane death’, i.e., euthanasia, was achieved. Each animal was shot using different projectile types: soft non-bonded, solid, and soft bonded. In two animals, insensibility was not immediately assessed following shooting, although both were reported as ‘instantaneously insensible’. From our analysis, all animals displayed musculoskeletal responses to shooting, including peduncle stiffening and slack lower jaw, followed by musculature relaxation 24-, 10.3- and 20.8-seconds post-ballistics, respectively. The animal shot with a soft non-bonded projectile also displayed agonal convulsions and tail-lifting for 16-seconds post-shot; these were not observed for solid or soft bonded projectiles. PMCT findings indicated projectile disruption to the brainstem and/or spinal cord likely to cause near-instantaneous insensibility. However, extra-cranial wounding was also evident for the soft non-bonded projectile, highlighting potential for additional welfare compromise. Our results demonstrate that ballistics can achieve a relatively rapid death in young, stranded cetaceans, but careful equipment selection is required. To ensure a humane death, verification of insensibility must be undertaken immediately following shooting. Further studies should be undertaken to improve knowledge of appropriate procedures and equipment for euthanasia, ensuring humane deaths for compromised cetaceans.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Adapting the CROPGRO Perennial Forage model to predict growth and development of Pensacola bahiagrass - Hunter D. Smith; Chris H. Wilson; Stuart J. Rymph; Erick R.S. Santos; Kenneth J. Boote (Field Crops Research, 2023)

Assessing animal welfare during a stranding of pygmy killer whales ( Feresa attenuata ) - Rebecca M. Boys; Ngaio J. Beausoleil; Stuart Hunter; Emma L. Betty; Bethany Hinton; Karen A. Stockin (Marine Mammal Science, 2023)
Empirical assessment of cetacean welfare to inform stranding interventions is lacking. Here, potential welfare indicators are described for two stranded pygmy killer whales ( Feresa attenuata ), along with euthanasia procedures and pathology of potential relevance. The animals were filmed for 3.5 and 1.5 hr, respectively, allowing assessment of 19 indicators, including animal behaviors and human interventions. Eight interventions and 19 animal behaviors were identified; 17 and 11 behaviors were displayed by animal 1 and 2, respectively. Examination of ballistics euthanasia revealed atypical projectile placement and characterized animal behavioral responses, but welfare implications could not be assessed as insensibility was not verified in‐field. Pulmonary edema and renal degeneration were documented in both animals; differential etiologies include ischemia–reperfusion, shock, and/or myopathy. Potential relationships among histopathology and welfare indicators are explored to infer affective experiences. For example, simultaneous head‐lifting with respiration increased over time which, alongside pulmonary edema, suggests these animals experienced breathlessness. Other likely affective states include fatigue and discomfort; there are insufficient data to estimate the intensity or duration of these experiences or to provide an overall welfare grade/score. Further data are required to validate the proposed welfare indicators and to progress development of holistic approaches to welfare assessment at cetacean strandings.

Frontiers of Mathematical Biology: A workshop honouring Professor Edmund Crampin - Robyn Araujo; Douglas Brumley; Joe Cursons; Karen Day; Matthew Faria; Jennifer A. Flegg; Domenic Germano; Hilary Hunt; Peter Hunter; Adrianne Jenner; Stuart Johnston; James M. McCaw; et al. (Mathematical Biosciences, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Papillomas and probable in situ carcinoma in association with a novel papillomavirus in a red-billed gull (Chroicocephalus novaehollandiae scopulinus) - John S. Munday; Mike R. Hardcastle; Stuart Hunter; Cathy J. Harvey (Archives of Virology, 2021)

The assessment of neuromuscular fatigue during 120 min of simulated soccer exercise - Stuart Goodall; Kevin Thomas; Liam David Harper; Robert Hunter; Paul Parker; Emma Stevenson; Daniel West; Mark Russell; Glyn Howatson (European Journal of Applied Physiology, 2017)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Adipokine expression and secretion by canine adipocytes: stimulation of inflammatory adipokine production by LPS and TNFα - Vivien H. Ryan; Alexander J. German; I. Stuart Wood; Leif Hunter; Penelope Morris; Paul Trayhurn (Pflügers Archiv - European Journal of Physiology, 2010)

Cloning, sequencing and analysis of the pucC genes from Rubrivivax gelatinosus strain 151 and Rhodopseudomonas acidophila strain 10050 - Adrian E. Simmons; Stuart J. Barrett; C. Neil Hunter; Richard J.R. Cogdell (Photosynthesis Research, 2000)